Literature Review of Fixed Asset Intensity on Tax Aggressiveness - Feni, Moi (CV. Proaksara Global Transeduka, 2024)
This study aims to examine the effect of fixed asset intensity on tax aggressiveness. Tax has become one of the problems that are widely handled in a country. One of the state revenues comes from taxes, without society there would be no taxes. Tax can be interpreted as a collection made by the government with the aim of realising a prosperous society. The independent variable in this study is fixed asset intensity, while the dependent variable is tax aggressiveness. The results showed that the fixed asset intensity variable did not all have a significant positive effect on tax aggressiveness.